PERAN NEUROSAINS DALAM PENINGKATAN TEKNIK HAFALAN AL-QUR’AN - Nurbazilah Sakynah Tahir; Husain, Muhammad zakir; Ahmad Baha’; Khairun Naqibah; Sarinah Yahya; Yusfariza Yussop (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2024)
This study discusses the role of neuroscience in Qur'an memorization learning and its relationship with Qur'an memorization techniques. However, most memorizers pay little attention to and do not understand the benefits of neuroscience in memorizing the Qur'an. In addition, the memorization techniques currently used focus solely on the learning aspect without being linked to neuroscience. Therefore, this study aims to identify brain functions and memory processes in Qur'an memorization learning and examine the relationship between neuroscience and Qur'an memorization techniques. To achieve these objectives, this study employs a literature review methodology to answer the research questions. The results of the study indicate that there is a relationship between neuroscience and Qur'an memorization techniques. By understanding the connection between neuroscience and Qur'an memorization, memorizers can improve the quality of their memorization. This study provides insight into the importance of understanding brain functions and memory processes for Quran memorizers. Memorization techniques can be adjusted based on neuroscience knowledge to enhance the effectiveness and quality of memorization.